2017
DOI: 10.1186/s12957-017-1171-y
|View full text |Cite
|
Sign up to set email alerts
|

Combining serum miRNAs, CEA, and CYFRA21-1 with imaging and clinical features to distinguish benign and malignant pulmonary nodules: a pilot study

Abstract: BackgroundOur study was designed to improve the accuracy of determining whether pulmonary nodules are benign or malignant.MethodsWe evaluated the clinical and imaging features and serum markers: neuron specific enolase (NSE), carcino-embryonic antigen (CEA), cytokeratin fragment antigen 21–1 (CYFRA 21–1), miRNA-21-5p, and miR-574-5pof in 39 patients with pathology information. Factors that differed significantly between those with benign versus malignant pulmonary nodules were used to establish a prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…26 Other studies have shown that lumps are more likely to be destructive if vessel convergence signs are present. 30 Furthermore, our models differed from other models in many ways, such as in target population and parameters. [18][19][20][21][22][23][24][25][26]31,32 On one hand, our models focused on patients with lung diseases and pleural effusion, in which 73.6% of cases were adenocarcinomatous in the lung cancer group, and 66.1% of subjects had tuberculosis in the benign group.…”
Section: Discussionmentioning
confidence: 96%
“…26 Other studies have shown that lumps are more likely to be destructive if vessel convergence signs are present. 30 Furthermore, our models differed from other models in many ways, such as in target population and parameters. [18][19][20][21][22][23][24][25][26]31,32 On one hand, our models focused on patients with lung diseases and pleural effusion, in which 73.6% of cases were adenocarcinomatous in the lung cancer group, and 66.1% of subjects had tuberculosis in the benign group.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, detecting miRNAs in serum was more convenience for clinical practice [ 79 , 80 ]. Also, combined miRNAs with serum protein markers, such as cytokeratin 19 fragment (CYFRA21-1), carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cancer-associated antigen (CA) 125 and CA 19-9 maybe more effective in the diagnosis of lung cancer [ 58 , 81 ]. We also conducted subgroup analysis based on the source of controls; the source of controls could be mainly divided into healthy population and cancer-free controls.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, traditional tumor-associated antigen (TAA) biomarkers, such as cytokeratin 19 fragment antigen 21-1 (CYFRA21-1), neuron-specific enolase (NSE), carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC), carbohydrate antigen (CA) 125, CA15-3, CA19-9, and CA72-4, remain widely used as reference diagnoses for lung cancer [ 9 , 10 ] (Isaksson, Jonsson et al 2017, Seijo, Peled et al 2019). Single markers have limited sensitivity and specificity, and combinations of tumor markers (TMs) can improve the diagnostic accuracy [ 12 15 ] (Yoon, Kwon et al 2016, Li, Zhang et al 2017, Liu, Teng et al 2017, Fang, Zhu et al 2018), but few studies have compared different panels of TAAs, and some of these biomarkers may be increased in patients with BLD. Therefore, the aim of this study was to identify the best potential combinations of these traditional tumor markers in distinguishing lung cancer patients from BLD controls.…”
Section: Introductionmentioning
confidence: 99%